Uranium immobilization method and its application in solid fuel cells
By fixing uranium into the new BaCe0.8-xUxY0.2O3 (BCUY) material, the problems of poor stability of uranyl minerals and insufficient stability of proton conductor electrolyte materials are solved, and effective immobilization of uranium and improved stability of electrolytes are achieved. , extends the service life of solid fuel cells and reduces maintenance costs.
Patent Information
- Application Number
- CN202111553284.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-18
- Filing Date
- 2021-12-17
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-12-17
AI Technical Summary
The chemical stability of existing uranyl minerals is poor, which can easily lead to uranium migration and environmental pollution. At the same time, the stability of the proton conductor electrolyte material BaCeO3 is also poor, affecting the life and maintenance cost of solid fuel cells.
UO2(NO3)2·6H2O, Ce(NO3)3·6H2O, Y(NO3)3·6H2O and barium salt soluble in nitric acid are dissolved in a molar ratio of specific elements, and then heat and dry after adding complexing agent. and high temperature calcination, a new BaCe0.8-xUxY0.2O3 (BCUY) material was prepared, which immobilized uranium and improved the stability of the electrolyte.
Effectively immobilize uranium, reduces its migration performance and environmental harm, while improving the chemical stability and conductivity of electrolytes, extending the service life of solid fuel cells and reducing maintenance costs.
Smart Images

Figure CN114243072B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of uranium immobilization and application, and in particular to a uranium immobilization method and application in a solid fuel cell. Background Art
[0002] Uranium is a natural radioactive element and one of the main sources of nuclear energy. It has an important strategic position and is increasingly valued by countries around the world. However, when people use nuclear energy, uranium is easily transferred into the environment. Uranium is chemically active and easily soluble in water. It has strong chemical toxicity and radioactivity, which can cause chronic poisoning, cancer and some immune system diseases, seriously threatening human health.
[0003] Uranium exists in nature in the form of uranium minerals. Uranium minerals can be divided into two categories according to their chemical composition: tetravalent uranium minerals and uranyl minerals. Among them, tetravalent uranium minerals are mostly black, gray-black, dark brown or dark green, and are radioactive; while uranyl minerals not only have strong chemical toxicity and radioactivity, but also have poor chemical stability, and are prone to uranium migration, causing environmental pollution. Therefore, it is extremely important to immobilize uranium and reduce uranium migration.
[0004] In order to solve the energy crisis and environmental problems, people have conducted a lot of exploration on new energy materials. Research has found that solid fuel cells have a wide range of uses, can be used as fixed power sources, can also be used as small mobile power sources, have high energy conversion rates, can be highly modularized, have large total installed capacity, and are flexible and convenient to install and select sites, which greatly alleviates people's dependence on traditional fuels.
[0005] Solid fuel cell monomers are mainly composed of anodes, electrolytes and functional layers. As the core component of solid oxide fuel cells, electrolytes play the role of conducting ions between the cathode and anode. Its performance (including conductivity, stability, thermal expansion coefficient, densification temperature, etc.) not only directly affects the operating temperature and conversion efficiency of the battery, but also determines the selection of electrode materials and their preparation technologies that need to match it. After the study found that BaCeO3 has high proton conductivity, the electrolyte of proton conductor materials has attracted more and more attention. At present, some studies have found that doping BaCeO3 with new elements can improve its conductivity; among them, doping Y element makes BaCeO3 (BCY) have excellent conductivity. However, although this material (BCY) has good conductivity, its stability is poor. Under the action of CO2 and H2S, CeO2 and corresponding carbonates are easily generated, which reduces the conductivity, reduces the life of the battery, increases its maintenance cost, and seriously limits its practical application value.
[0006] In view of this, it is necessary to design an improved uranium immobilization method and its application in solid fuel cells to solve the above problems. Summary of the invention
[0007] The purpose of the present invention is to provide a method for immobilizing uranium and its application in solid fuel cells. By fixing uranium into BCY material, a new BCUY material used as a proton conductor electrolyte is prepared; the uranium can be immobilized, the migration performance of uranium can be reduced, and its harm to the surrounding environment can be reduced, and the defect of poor stability of BCY can be improved, which has high practical application value.
[0008] To achieve the above-mentioned invention object, the present invention provides a method for immobilizing uranium and its application in a solid fuel cell. Among them, a method for immobilizing uranium comprises the following steps:
[0009] S1. Dissolve UO2(NO3)2·6H2O, Ce(NO3)3·6H2O, Y(NO3)3·6H2O and a barium salt soluble in nitric acid and easily decomposed at high temperature in deionized water according to a certain element molar ratio, and obtain a mixed solution after complete dissolution; the element molar ratio is Ba:Ce:U:Y=1:(0.8-x):x:0.2, wherein 0.05≤x≤0.2;
[0010] S2, adding a complexing agent to the mixed solution obtained in step S1, then adding ammonia water to adjust the pH of the solution to 8-9, and continuously stirring the mixed solution;
[0011] S3, placing the mixed solution stirred in step S2 in a crucible, heating and drying until no white smoke comes out, to obtain a yellow-brown precursor;
[0012] S4, calcining the yellow-brown precursor obtained in step S3 in a muffle furnace at a temperature of 1100-1400° C. for 6-8 hours to obtain a novel BaCe 0.8-x U x Y 0.2 O3 material.
[0013] As a further improvement of the present invention, the molar ratio of the added amount of the complexing agent to the metal ions in the mixed solution is (1.5-2):1.
[0014] As a further improvement of the present invention, in step S1, the barium salt is one or more of barium carbonate, barium nitrate and barium acetate.
[0015] As a further improvement of the present invention, the complexing agent is citric acid.
[0016] As a further improvement of the present invention, in step S1, the UO2(NO3)2·6H2O can be prepared from one or more of uranium salts, uranium minerals and secondary uranium minerals.
[0017] As a further improvement of the present invention, in step S2, the continuous stirring time is 5 to 7 hours so that the solution can be fully mixed.
[0018] A method for immobilizing uranium in a solid fuel cell, wherein the novel BaCe is prepared by the immobilization method of uranium described in any one of the above items. 0.8-x U x Y 0.2 O3 materials are used as electrolyte materials in solid fuel cells.
[0019] As a further improvement of the present invention, the method for applying uranium in a solid fuel cell comprises: pre-calcining the yellow-brown precursor described in any of the above items in a microwave muffle furnace, then mixing it with anode powder and pressing it into a half-cell, and then calcining it at 1100-1400°C for 6-8h.
[0020] As a further improvement of the present invention, the temperature of the pre-calcination treatment is 900-1000° C. and the time is 1-1.5 hours.
[0021] The beneficial effects of the present invention are:
[0022] 1. The uranium immobilization method and application in solid fuel cells provided by the present invention are as follows: UO2(NO3)2·6H2O, Ce(NO3)3·6H2O, Y(NO3)3·6H2O and a barium salt soluble in nitric acid and easily decomposed at high temperature are dissolved in deionized water, and a complexing agent is added, and a yellow-brown precursor is obtained after heating and drying; the precursor is calcined and solidified to obtain a new BaCe 0.8- x U x Y 0.2 O3 (BCUY) material, BCUY material as a new proton conductor electrolyte material can be used in solid fuel cells. The present invention can not only immobilize uranium, greatly reduce the migration performance of uranium, reduce its harm to the environment, but also improve the defect of poor stability of existing electrolyte material BCY, and has high practical application value.
[0023] 2. The method adopted by the present invention can better fix the axis, and the UO2(NO3)2·6H2O used can be prepared from discarded uranium salts, uranium minerals or secondary uranium minerals, and its raw material sources are wide. It not only achieves the recycling of waste resources and has the significance of green environmental protection, but also provides a new way for the practical application of uranium in solid fuel cells.
[0024] 3. In the present invention, a high-temperature calcination process is used to fix uranium to obtain BCUY material; during high-temperature calcination, uranium can be better fixed in the lattice structure of the material; and the new material BCUY finally obtained has better chemical stability and higher economic benefits compared with the existing electrolyte material BCY; BCUY material as a new electrolyte material for preparing solid fuel cells has higher application value and longer service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The BaCe prepared in Example 1 of the present invention 0.7 U 0.1 Y 0.2 XRD results of O3 material.
[0026] Figure 2 The results of high-temperature in-situ XRD tests of materials at 600°C and carbon dioxide atmosphere at different times; (a) is BCY material, (b) is the new BaCe prepared in Example 1 0.7 U 0.1 Y 0.2 O3 material.
[0027] Figure 3 This is the impedance spectrum of the half-cell made of BCUY material in Example 4 of the present invention.
[0028] Figure 4 This is a diagram showing the conductivity test results of a half-cell made of BCUY material in Example 4 of the present invention.
[0029] Figure 5 This is a cross-sectional electron microscope image of a half-cell made of BCUY material in Example 4 of the present invention.
[0030] Figure 6 This is a surface electron microscope image of a half-cell made of BCUY material in Example 4 of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0032] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0033] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0034] A method for immobilizing uranium comprises the following steps:
[0035] S1. Dissolve UO2(NO3)2·6H2O, Ce(NO3)3·6H2O, Y(NO3)3·6H2O and a barium salt soluble in nitric acid and easily decomposed at high temperature in deionized water according to a certain element molar ratio, and obtain a mixed solution after complete dissolution; wherein the element molar ratio is Ba:Ce:U:Y=1:(0.8-x):x:0.2, 0.05≤x≤0.2;
[0036] In particular, the barium salt is one or more of barium carbonate, barium nitrate and barium acetate. The UO2(NO3)2·6H2O used is prepared from one or more of uranium salts, uranium minerals and secondary uranium minerals, and its raw material sources are extensive; it not only achieves the recycling of waste resources, has the significance of green environmental protection, but also provides a new way for the practical application of uranium in solid fuel cells.
[0037] S2, adding a complexing agent to the mixed solution obtained in step S1, and then quickly adding ammonia water to adjust the pH of the solution to 8-9, and continuously stirring the mixed solution for 5-7 hours so that the solution is fully mixed;
[0038] Specifically, the molar ratio of the amount of the complexing agent added to the metal ions in the mixed solution is (1.5-2):1; the complexing agent is citric acid; citric acid is widely distributed in nature, and its raw material cost is relatively low. The addition of the complexing agent can promote the binding of metal ions, which is conducive to the subsequent preparation of a stable crystal structure.
[0039] S3, placing the mixed solution stirred in step S2 in a crucible, heating and drying until no white smoke comes out, to obtain a yellow-brown precursor;
[0040] S4, calcining the yellow-brown precursor obtained in step S3 in a muffle furnace at a temperature of 1100-1400° C. for 6-8 hours to obtain BaCe 0.8-x U x Y 0.2 O3 material.
[0041] In particular, uranium is fixed by a high-temperature calcination process to obtain BCUY material, which can be better fixed in the lattice structure of the material during high-temperature calcination; and the new material BCUY finally obtained has better chemical stability and higher economic benefits compared with the existing electrolyte material BCY; BCUY material as a new electrolyte material for preparing solid fuel cells has higher application value and longer service life.
[0042] An application of uranium in a solid fuel cell, wherein BaCe is prepared by the uranium immobilization method of any one of the above items. 0.8- x U x Y 0.2 O3 materials are used as new electrolyte materials in solid fuel cells.
[0043] Specifically, the method for applying uranium in a solid fuel cell includes: pre-calcining the above-mentioned yellow-brown precursor in a microwave muffle furnace, then mixing it with anode powder and pressing it into a half-cell, and then calcining it at 1100-1400°C for 6-8 hours. The pre-calcination temperature is 900-1000°C and the time is 1-1.5 hours.
[0044] Example 1
[0045] Example 1 provides a method for immobilizing uranium, comprising the following steps:
[0046] S1. Dissolve UO2(NO3)2·6H2O, Ce(NO3)3·6H2O, Y(NO3)3·6H2O and barium carbonate in deionized water according to a certain element molar ratio, and obtain a mixed solution after complete dissolution; wherein the element molar ratio is Ba:Ce:U:Y=1:0.7:0.1:0.2;
[0047] S2, adding citric acid in a molar ratio of 1.5:1 to the metal ions in the mixed solution to the mixed solution prepared in step S1, and after the citric acid is completely dissolved, quickly adding ammonia water to adjust the pH of the solution until the pH is 8, and continuously stirring the mixed solution for 6 hours so that the solution is fully mixed;
[0048] S3, placing the mixed solution stirred in step S2 in a crucible, heating and drying until no white smoke comes out, to obtain a yellow-brown precursor;
[0049] S4, calcining the yellow-brown precursor obtained in step S3 in a muffle furnace at a calcination temperature of 1100° C. for 6 h to obtain BaCe 0.7 U 0.1 Y 0.2 O3 material.
[0050] See also Figure 1 As shown, Figure 1 The BaCe prepared in Example 1 0.8-x U x Y 0.2 The XRD result diagram of O3 material shows that uranium is well fixed in the lattice structure, which greatly reduces its migration performance and reduces its harm to the environment and people's lives.
[0051] The BaCe prepared in Example 1 0.7 U 0.1 Y 0.2 The O3 material was tested continuously for 6 hours by high temperature in-situ XRD at 600°C in a carbon dioxide atmosphere (10% CO2 + 90% air). The test results are as follows: Figure 2 (b) is shown. Figure 2 As shown in (b), after 6 hours of high temperature, no new substances were generated and no uranium was precipitated. Figure 2 (a) is the XRD test result of BCY material under the same conditions. Compared with Figure (a), it can be seen that this method can not only fix uranium well, but also improve the stability of BaCeO3, so that it can be used as an electrolyte material for solid fuel cells.
[0052] Example 2-3
[0053] Example 2-3 provides a method for immobilizing uranium. Compared with Example 1, the difference is that in step S1, the molar ratio of the elements in Example 2 is Ba:Ce:U:Y=1:0.75:0.05:0.2, and BaCe is obtained. 0.75 U 0.05 Y 0.2 O3 material; the molar ratio of the elements in Example 3 is Ba:Ce:U:Y=1:0.65:0.15:0.2, and BaCe is obtained 0.65 U 0.15 Y 0.2 O3 material; the rest is substantially the same as in Example 1 and will not be described again.
[0054] Example 4
[0055] The present invention provides an application of uranium in a solid fuel cell, comprising the following steps:
[0056] S1. Dissolve UO2(NO3)2·6H2O, Ce(NO3)3·6H2O, Y(NO3)3·6H2O and barium carbonate in deionized water according to a certain element molar ratio, and obtain a mixed solution after complete dissolution; wherein the element molar ratio is Ba:Ce:U:Y=1:0.7:0.1:0.2;
[0057] S2, adding citric acid in a molar ratio of 1.5:1 to the metal ions in the mixed solution to the mixed solution prepared in step S1, and after the citric acid is completely dissolved, quickly adding ammonia water to adjust the pH of the solution until the pH is 8, and continuously stirring the mixed solution for 6 hours so that the solution is fully mixed;
[0058] S3, placing the mixed solution stirred in step S2 in a crucible, heating and drying until no white smoke comes out, to obtain a yellow-brown precursor;
[0059] S4. The yellow-brown precursor obtained in step S3 is placed in a microwave muffle furnace and pre-calcined at 950°C for 1 hour. Then, the anode powder and the precursor pre-treated in the microwave muffle furnace are pressed into a half-cell according to the co-pressing and co-firing method. Finally, the pressed half-cell is placed in a muffle furnace and calcined at 1350°C for 6 hours to obtain a calcined half-cell.
[0060] The half-cell after high temperature calcination was dotted with porous silver. The impedance was measured at 50°C intervals from 700°C under the condition of wet H2 by an electrochemical workstation, and the conductivity was calculated. The measurement end temperature was 400°C. Please refer to Figure 3 The impedance spectrum is shown in Figure 2. Figure 4 The following is a graph showing the conductivity test results. Figure 3 and Figure 4 It can be seen that when the test temperature is 700℃, its conductivity is 2.82×10 -3 S / cm, still has good electrochemical performance, indicating that the new BaCe 0.8-x U x Y 0.2 Batteries using O3 as electrolyte material have better performance.
[0061] See also Figure 5-Figure 6 As shown, Figure 5 , Figure 6 The cross-section and surface electron microscope images of the half-cell made of BCUY material in Example 4 of the present invention are shown respectively. It can be seen that the half-cell after high-temperature calcination is relatively dense, contains a small amount of closed pores, and the surface grains are relatively small and dense, ensuring the long-term and stable application of the battery.
[0062] Embodiment 5-6
[0063] Example 5-6 provides an application of uranium in a solid fuel cell. Compared with Example 4, the difference is that in step S1, the molar ratio of the elements in Example 5 is Ba:Ce:U:Y=1:0.75:0.05:0.2, and BaCe is obtained. 0.75 U 0.05 Y 0.2O3 material; the molar ratio of the elements in Example 6 is Ba:Ce:U:Y=1:0.65:0.15:0.2, and BaCe is obtained 0.65 U 0.15 Y 0.2 O3 material; the rest is substantially the same as in Example 4 and will not be described again.
[0064] In summary, the present invention provides a method for immobilizing uranium and its application in a solid fuel cell, wherein UO2(NO3)2·6H2O, Ce(NO3)3·6H2O, Y(NO3)3·6H2O and a barium salt soluble in nitric acid and easily decomposed at high temperature are dissolved in deionized water, a complexing agent is added, and a yellow-brown precursor is obtained after heating and drying; the precursor is calcined and solidified to obtain a novel BaCe 0.8-x U x Y 0.2 O3 (BCUY) material, BCUY material can be used in solid fuel cells as a new proton conductor electrolyte material. The UO2 (NO3) 2·6H2O used can be prepared from discarded uranium salts, uranium minerals or secondary uranium minerals, and its raw material sources are wide; it not only achieves the recycling of waste resources and has the significance of green environmental protection, but also provides a new way for the practical application of uranium in solid fuel cells. In addition, the present invention can not only immobilize uranium very well, greatly reduce the migration performance of uranium, reduce its harm to the surrounding environment, but also improve the defects of poor stability of the existing electrolyte material BCY; the new material BCUY finally obtained has better chemical stability and higher economic benefits compared with the existing electrolyte material BCY; the solid fuel cell prepared with BCUY material as a new electrolyte material has higher application value and longer service life.
[0065] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for immobilizing uranium, characterized in that: The following steps are involved: S1. Dissolve UO2(NO3)2·6H2O, Ce(NO3)3·6H2O, Y(NO3)3·6H2O and a barium salt soluble in nitric acid and easily decomposed at high temperature in deionized water according to a certain element molar ratio, and obtain a mixed solution after complete dissolution; the element molar ratio is Ba:Ce:U:Y=1:(0.8-x):x:0.2, wherein 0.05≤x≤0.2; S2, adding a complexing agent to the mixed solution obtained in step S1, then adding ammonia water to adjust the pH of the solution to 8-9, and continuously stirring the mixed solution; S3, placing the mixed solution stirred in step S2 in a crucible, heating and drying until no white smoke comes out, to obtain a yellow-brown precursor; S4, calcining the yellow-brown precursor obtained in step S3 in a muffle furnace at a calcination temperature of 1100-1400° C. for 6-8 hours to obtain a new BaCe 0.8-x U x Y 0.2 O3 material; the new BaCe 0.8-x U x Y 0.2 O3 materials are used as electrolyte materials in solid fuel cells.
2. The method for immobilizing uranium according to claim 1, characterized in that: In step S2, the molar ratio of the added amount of the complexing agent to the metal ions in the mixed solution is (1.5-2):
1.
3. The method for immobilizing uranium according to claim 1, characterized in that: In step S1, the barium salt is one or more of barium carbonate, barium nitrate and barium acetate.
4. The method for immobilizing uranium according to claim 1, characterized in that: The complexing agent is citric acid.
5. The method for immobilizing uranium according to claim 1, characterized in that: In step S1, the UO2(NO3)2·6H2O is prepared from one or more of uranium salts, uranium minerals and secondary uranium minerals.
6. The method for immobilizing uranium according to claim 1, characterized in that: In step S2, the continuous stirring time is 5 to 7 hours so that the solution can be fully mixed.
7. The method for immobilizing uranium according to claim 1, characterized in that: The method for applying uranium in a solid fuel cell comprises: pre-calcining the yellow-brown precursor described in any one of claims 1 to 6 in a microwave muffle furnace, then mixing it with anode powder and pressing it into a half-cell, and then calcining it at 1100-1400°C for 6-8h.
8. The method for immobilizing uranium according to claim 7, characterized in that: The pre-calcination treatment is carried out at a temperature of 900-1000° C. and for a time of 1-1.5 hours.
Citation Information
Patent Citations
Electrolyte for solid oxide fuel cell and preparation method thereof
CN103746134A
Proton conducting intermediate temperature solid oxide fuel cell electrolyte and preparation method thereof
CN106920979A
Method for obtaining nanoparticulated ashes of actinide, lanthanide, metal and non-metal oxides from a nitrate solution or from a nitrate, oxide, metal and non-metal suspension
WO2021019319A1